2005
DOI: 10.1007/s00125-004-1635-9
|View full text |Cite
|
Sign up to set email alerts
|

The negative association between plasma ghrelin and IGF-I is modified by obesity, insulin resistance and type 2 diabetes

Abstract: Aims/hypothesis: Ghrelin is a natural growth hormone-releasing peptide thought to be involved in the regulation of energy metabolism. The recent studies concerning the association between ghrelin and insulin-like growth factor-I (IGF-I) concentrations have shown either negative correlation or no correlation at all. The aims of this study were to clarify the association between ghrelin and IGF-I concentrations in a large cohort and to characterize whether obesity, insulin resistance and type 2 diabetes affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…This finding is supported by previous studies. 21 , 29 It has shown that as the number of components of MetS increased, a progressive elevation in plasma acylated ghrelin and a decrease in plasma desacyl ghrelin were observed. 30 Desacyl ghrelin is the major circulating form and acts as an antagonist of acylated ghrelin.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by previous studies. 21 , 29 It has shown that as the number of components of MetS increased, a progressive elevation in plasma acylated ghrelin and a decrease in plasma desacyl ghrelin were observed. 30 Desacyl ghrelin is the major circulating form and acts as an antagonist of acylated ghrelin.…”
Section: Discussionmentioning
confidence: 99%
“…Since a direct effect of maternal ghrelin on cord blood IGF-I is unlikely, we speculate that maternal ghrelin signaled decreased levels of nutrients available for placental transfer, which were associated with decreased cord blood IGF-I and IGFBP3. This could be compared to the inverse relationship between circulating ghrelin and IGF-I described in studies in children and adults [39,40,41]. Interestingly, ghrelin administration in pregnant rats has been shown to cause an increase in birth weight of their newborns by an unknown mechanism [14].…”
Section: Discussionmentioning
confidence: 99%
“…The orexigenic actions of ghrelin require the activation of hypothalamic sirtuin-1 (SIRT1) / p53, AMP-activated protein kinase (AMPK), and mammalian target of rapamycin (mTOR) pathways, which ultimately increase NPY and AgRP expression in the arcuate nucleus [ 48 , 49 , 50 ]. Despite its orexigenic effect, obesity, insulin resistance, type 2 diabetes, and the metabolic syndrome are related to a paradoxical decrease in circulating ghrelin levels [ 7 , 51 , 52 ]. However, these pathologies are associated with a dramatic reduction of plasma desacyl ghrelin concentrations, the most abundant form of the hormone, while plasma levels of acylated ghrelin remain unchanged or increased [ 19 , 53 , 54 , 55 ].…”
Section: The Role Of Leptin and Ghrelin In The Regulation Of Body Weimentioning
confidence: 99%